Anaesthesia management in a patient of interstitial lung disease with pulmonary hypertension for emergency laparotomy - Parekh, Hardik A.; Latkar, Prajakta D.; Nalavade, Ameya G.; Mehta, Hemant H. (International Journal of Research in Medical Sciences, 2021)
We report the anesthaetic management of a patient with known case of interstitial lung disease (ILD) with profound fibrotic changes and bullae with severe pulmonary hypertension (PH) posted for exploratory laparotomy for cecal volvulus. Emergency exploratory laparotomy was done under combined spinal-epidural anaesthesia to avoid intra-operative and post-operative pulmonary complications associated with general anaesthesia and mechanical ventilation.